2008
DOI: 10.1007/s10778-008-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Resonant electromechanical vibrations of piezoelectric shells of revolution (review)

Abstract: Scientific results from studies on the resonant electromechanical vibrations of piezoceramic thin-walled shells of revolution, their fragments, and segmented cylinders are analyzed, systematized, and generalized. Considerable attention is focused on experimental studies of resonant vibrations. It is shown that the modes in which deformation occurs inphase throughout the volume are of the highest intensity in all piezoceramic shell structures Introduction. The modern piezoelectric transducers employ either dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Piezoelectric circular thin-walled elements are used in various ultrasonic devices. The axisymmetric radial vibrations of thin piezoceramic disks and ring plates with thickness polarization were studied in many publications [1,4,5,7,8,10,11,13,14] beginning with [12]. However, no systematic analysis of the influence of the boundary conditions on the resonant frequencies has been performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Piezoelectric circular thin-walled elements are used in various ultrasonic devices. The axisymmetric radial vibrations of thin piezoceramic disks and ring plates with thickness polarization were studied in many publications [1,4,5,7,8,10,11,13,14] beginning with [12]. However, no systematic analysis of the influence of the boundary conditions on the resonant frequencies has been performed.…”
mentioning
confidence: 99%
“…In the axisymmetric plane case, of the three vibration equations in cylindrical coordinates, only the following is used [6,8] [6] in terms of first-order cylindrical Bessel functions of the first and second kinds: …”
mentioning
confidence: 99%
“…The test specimen is made by joining a spherical shell and a cylinder. We will also use the piezotransformer transducer method (PTTM) repeatedly described in the literature [2,3,7,11]. In particular, it will be shown that the deformation of the spheroid is asymmetric at all strong resonances, even though the specimen is geometrically axisymmetric.…”
mentioning
confidence: 99%
“…The electromechanical vibrations of spherical and spheroidal piezoceramic structures, including a cylinder joined to a closed spherical shell or to an open spherical shell (made by removing a cylindrical portion from a compound spheroid) were studied on [11]. Comparing Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation